2014
DOI: 10.1038/bmt.2014.280
|View full text |Cite
|
Sign up to set email alerts
|

Baseline body mass index among children and adults undergoing allogeneic hematopoietic cell transplantation: clinical characteristics and outcomes

Abstract: Obesity is an important public health problem that may influence the outcomes of hematopoietic cell transplantation (HCT). We studied 898 children and adults receiving first-time allogeneic hematopoietic stem cell transplants between 2004 and 2012. Pre-transplant body mass index (BMI) was classified as underweight, normal weight, overweight, or obese using the WHO classification, or age-adjusted BMI percentiles for children. The study population was predominantly Caucasian, and the median age was 51 years (5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…ST2 was also included in a biomarkers panel predictive for cGvHD development, GvHD severity and TRM [24]. Finally, pretransplant ST2 levels were reported being higher in obese patients as compared to normal weight patients [25]. Our result displayed that soluble ST2 levels increased from baseline to both aGvHD and cGvHD onset, but no differences were seen in terms of response to treatment.…”
Section: Discussionmentioning
confidence: 58%
“…ST2 was also included in a biomarkers panel predictive for cGvHD development, GvHD severity and TRM [24]. Finally, pretransplant ST2 levels were reported being higher in obese patients as compared to normal weight patients [25]. Our result displayed that soluble ST2 levels increased from baseline to both aGvHD and cGvHD onset, but no differences were seen in terms of response to treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Pretransplantation plasma ST2 levels were higher in obese transplant recipients, as were subsequent nonrelapse mortality rates, most commonly from acute and chronic GVHD [52], indicating a possible connection between the inflammatory processes associated with obesity/MetSyn and GVHD.…”
Section: The Immune System As a Mediator Of Metabolic Syndromementioning
confidence: 99%
“…Zeyda et al found elevated ST2 and IL-33 expression in omental and subcutaneous adipose tissue as well as increased plasma sST2 in severely obese subjects as compared to lean controls [9]. Gleimer et al also revealed higher sST2 in obese patients than in normal weight patients among children and adults undergoing hematopoietic cell transplantation [38]. However, the dynamic of circulating sST2 as well as its correlation with clinical and laboratory parameters before and after bariatric surgery was not studied before.…”
Section: Discussionmentioning
confidence: 99%